2006
DOI: 10.1590/s0101-81752006000100009
|View full text |Cite
|
Sign up to set email alerts
|

Estrutura populacional da Balaenoptera bonaerensis (Burmeister) (Cetacea, Balaenopteridae) nas áreas de reprodução do Oceano Atlântico Sul

Abstract: Um estudo da composição dos grupos de baleias minke, Balaenoptera bonaerensis (Burmeister, 1867), capturadas nas águas de Costinha, Paraíba, Brasil, na época da caça comercial, foi realizado com o objetivo de conhecer a dinâmica dos principais parâmetros biológicos, assim como aspectos do comportamento reprodutivo desta espécie. Foram analisados dados da caça coletados pela Superintendência para o Desenvolvimento da Pesca e Companhia de Pesca Norte do Brasil acerca do tamanho e composição dos grupos, proporçõe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
2
3
0
Order By: Relevance
“…Although adults normally have lower mortality rates when compared to young and old individuals in different mammal species (Caughley, 1966), the proportion of juveniles found here and the fact that it is a birth area may indicate the segregation of mature males and females without offspring. Segregation related to age class has been previously suggested for common minke whale in Brazilian waters based on information from strandings and accidentally caught individuals (Zerbini et al, 1997;Secchi et al, 2003), and for Antarctic minke whale based on catch data (Lucena, 2006). The amount of data presented here reinforces this hypothesis of age class segregation, although juveniles and calves of common minke whale are also found in other places in Brazil (e.g., Geise & Borobia, 1988;Siciliano et al 2008;Santos et al, 2010).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Although adults normally have lower mortality rates when compared to young and old individuals in different mammal species (Caughley, 1966), the proportion of juveniles found here and the fact that it is a birth area may indicate the segregation of mature males and females without offspring. Segregation related to age class has been previously suggested for common minke whale in Brazilian waters based on information from strandings and accidentally caught individuals (Zerbini et al, 1997;Secchi et al, 2003), and for Antarctic minke whale based on catch data (Lucena, 2006). The amount of data presented here reinforces this hypothesis of age class segregation, although juveniles and calves of common minke whale are also found in other places in Brazil (e.g., Geise & Borobia, 1988;Siciliano et al 2008;Santos et al, 2010).…”
Section: Discussionsupporting
confidence: 82%
“…The results show that the northern coast of Rio Grande do Sul State is regularly inhabited by species of the genus Balaenoptera, as reported in adjacent areas (Prado et al, 2016) and in offshore waters of the continental slope (Di Tullio et al, 2016). In this context, environmental characteristics that result in high local productivity (Castello et al, 1998;Crespo, 2009) and the geographical position between areas of higher and lower latitudes used by these species at different stages of life (Lucena, 2006;Andriolo et al, 2010) may favor their occurrence in the study area. The low frequency of strandings of Antarctic minke and fin whales could be related to the species' offshore habitat (Di Tullio et al, 2016), which reduces the probability of their carcasses reaching the coast.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Examination of reproductive organs of whales processed in Costinha showed that both males and females were reproductively active off Brazil (WILLIAMSON 1975, DA ROCHA & BRAGA 1982, LUCENA 2006. Despite that, minke whale calves are not easily observed, which is unusual for an area considered a breeding ground.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, the northeast region has been considered a breeding area for the species (Horwood, 1990;Lucena, 2006), and individuals are often sighted in oceanic waters between 200 and 1,000 m depth and in greater numbers between August and October (Andriolo et al, 2010). This species is listed as data deficient by the International Union for Conservation of Nature (IUCN) (Reilly et al, 2008), and it is currently the most abundant mysticete in the Southern Hemisphere (Beekmans et al, 2010).…”
mentioning
confidence: 99%